2018
DOI: 10.1093/ntr/nty025
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Tobacco Product Use and Correlates Among Adults in the Population Assessment of Tobacco and Health (PATH) Study: A Latent Class Analysis

Abstract: IntroductionAs the tobacco industry and market evolves, there is a growing need to understand the patterns of use of tobacco products and how they relate to demographics, dependency, withdrawal, and quit behavior.MethodsWe analyzed data from wave 1 of the PATH Study consisting of 14856 individuals. Current users were defined as consuming at least 1 of 10 tobacco products. We performed a latent class analysis (LCA) to identify patterns of tobacco use. We used multinomial regression analysis to explore the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“… 25 In contrast, users of e-cigarettes and hookah were the youngest and most educated of all four use groups and showed the lowest dependency and least withdrawal symptoms. 25 Sung et al analyzed patterns of tobacco use and dependence items from 2012 to 2013 and 2013 to 2014 of the National Adult Tobacco Surveys and found that after controlling for frequency of use and demographic covariates, dependence ratings were higher among polytobacco users compared with exclusive tobacco users and this finding was consistent across all symptom measures for each category of tobacco user. 26 Focusing on the products themselves, Reilly et al examined two brands each of little cigars and filtered cigars, as well as two research cigarettes for carbonyl delivery and found that cigar smokers are exposed to higher levels of carbonyls per cigar than cigarette smokers per cigarette.…”
Section: Addiction and Toxicitymentioning
confidence: 93%
See 3 more Smart Citations
“… 25 In contrast, users of e-cigarettes and hookah were the youngest and most educated of all four use groups and showed the lowest dependency and least withdrawal symptoms. 25 Sung et al analyzed patterns of tobacco use and dependence items from 2012 to 2013 and 2013 to 2014 of the National Adult Tobacco Surveys and found that after controlling for frequency of use and demographic covariates, dependence ratings were higher among polytobacco users compared with exclusive tobacco users and this finding was consistent across all symptom measures for each category of tobacco user. 26 Focusing on the products themselves, Reilly et al examined two brands each of little cigars and filtered cigars, as well as two research cigarettes for carbonyl delivery and found that cigar smokers are exposed to higher levels of carbonyls per cigar than cigarette smokers per cigarette.…”
Section: Addiction and Toxicitymentioning
confidence: 93%
“…Analyzing Wave 1 PATH Study data, Kypriotakis et al performed Latent Class Analysis (LCA) to identify four patterns of tobacco use and examined the association between these patterns with a set of covariates representing socioeconomic status, dependence/addiction, past quit attempts, and withdrawal severity. 25 Results showed that exclusive cigarette users were more likely to be older and female, and experience higher dependence and greater withdrawal symptoms. 25 In contrast, users of e-cigarettes and hookah were the youngest and most educated of all four use groups and showed the lowest dependency and least withdrawal symptoms.…”
Section: Addiction and Toxicitymentioning
confidence: 98%
See 2 more Smart Citations
“…Further, AA are more likely to be poly-tobacco users (Kong et al, 2019; Mead et al, 2018) and co-use of cigarillos and cannabis is more frequent than using tobacco alone (Montgomery, 2015). These co-use patterns may compound the negative consequences of cigar smoking among AA and contribute to disproportionate disease burden (Cohn et al, 2015; Kypriotakis et al, 2018).…”
mentioning
confidence: 99%